Electrical Characterization of the Influence of the Annealing Energy Density on Carrier Lifetimes in Germanium. (1st January 2016) - Filippone, Bruno; Donaldson, Conor; Shayesteh, Maryam; O'Connell, Dan; Huet, Karim; Toqué-Tresonne, Ines; Crupi, Felice; Duffy, Ray
Abstract : In this work the authors examine the influence of the annealing energy density on carrier lifetime of n + /p Ge diodes processed by laser thermal annealing (LTA) and rapid thermal annealing (RTA). Current-voltage and capacitance-voltage measurements have been performed, and subsequently the reverse current and capacitance were separated into bulk and peripheral components to extract carrier lifetime: this allows the estimation of the bandgap position of the generation-recombination centres. The results indicate that the generation lifetime increases with increasing laser anneal energy density, coinciding with better crystal quality.